2019
DOI: 10.1103/physrevb.100.125432
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity at metal-antiferromagnetic insulator interfaces

Abstract: Magnons in antiferromagnetic insulators couple strongly to conduction electrons in adjacent metals. We show that this interfacial tie can lead to superconductivity in a tri-layer consisting of a metal sandwiched between two antiferromagnetic insulators. The critical temperature is closely related to the magnon gap, which can be in the THz range. We estimate the critical temperature in MnF2-Au-MnF2 to be on the order of 1 K. The Umklapp scattering at metal-antiferromagnet interfaces leads to a d-wave supercondu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 35 publications
0
49
0
Order By: Relevance
“…The processes where the momentum of the outgoing electron is shifted by a reciprocal lattice vector G are Umklapp processes. These processes are expected to be important for inducing superconductivity mediated by antiferromagnetic magnons in normal metals at half-filling [15]. For a tight-binding model, on a square lattice, at half-filling, G connects different points on the Fermi surface.…”
Section: And Fourier Transformations Of the Magnon Operators Amentioning
confidence: 99%
“…The processes where the momentum of the outgoing electron is shifted by a reciprocal lattice vector G are Umklapp processes. These processes are expected to be important for inducing superconductivity mediated by antiferromagnetic magnons in normal metals at half-filling [15]. For a tight-binding model, on a square lattice, at half-filling, G connects different points on the Fermi surface.…”
Section: And Fourier Transformations Of the Magnon Operators Amentioning
confidence: 99%
“…These excitations are quasiparticles known as magnons. Theoretical predictions of electron-magnon interactions have shown that these can also induce effects such as superconductivity [1][2][3][4][5][6][7][8][9][10].Research interest in antiferromagnetic materials is surging [11,12]. This enthusiasm is due to the promising properties of antiferromagnets such as high resonance frequencies in the THz regime and a vanishing net magnetic moment.…”
mentioning
confidence: 99%
“…These excitations are quasiparticles known as magnons. Theoretical predictions of electron-magnon interactions have shown that these can also induce effects such as superconductivity [1][2][3][4][5][6][7][8][9][10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have investigated whether spin fluctuations in a magnetic material can induce attractive interactions between electrons in an adjacent conductor, leading to a superconducting instability [1][2][3][4][5][6][7][8]. Both ferromagnetic (FMIs) and antiferromagnetic insulators (AFMIs) have been considered as potential sources for the magnetic fluctuations.…”
Section: Introductionmentioning
confidence: 99%